Шляхи вдосконалення законодавства, яке визначає правові засади соціального захисту учасників бойових дій - Митько, Є. В.; Mytko, Ye. V. (Науковий вісник публічного та приватного права. - 2019. - Вип. 2, т. 1. - С. 154-159, 2019)
Визначено можливі шляхи вдосконалення законодавства, яке визначає правові засади соціального захисту учасників бойових дій. Наголошено, що вирішити більшість наявних проблем можливо через уніфікацію відповідного законодавства шляхом прийняття єдиного кодифікованого нормативно-правового акта, а саме – «Основ законодавства про соціальний захист учасників бойових дій та їхніх сімей».

In the article based on the analysis of scientific views of scientists and the norms of the current legislation of Ukraine possible ways of improving legislation, which defines the legal principles of social protection of combatants. It was emphasized that the majority of existing problems could be solved by unification of the relevant legislation by adopting a single codified normative legal act, namely: “Fundamentals of legislation on social protection of participants in combat operations and their families”. It is emphasized that according to the draft Military Medical Doctrine its purpose is to create an accessible, universal, multi-disciplinary, effective system of medical supply of troops, which provides for the provision of medical assistance on a territorial basis and will allow to prevent, limit and minimize the scale of destruction of troops in peacetime and wartime by creating guaranteed capabilities for organized response to the military medical force. It is concluded that the solution of most existing problems of social protection of combatants is possible through the unification of the relevant legislation by adopting a single codified legal act, namely: “Fundamentals of legislation on social protection of combatants and their families”. These bases should combine the provisions of numerous regulations in this area, and at the same time determine: the legal status of combatants and their families; social guarantees and benefits for UBD; determine the mechanism for obtaining the relevant benefits and social security; outline the subjects and their powers in the field of social protection of the participants of the war, which will help to avoid duplication of their rights and responsibilities; to determine the responsibility of the state for the non-performance and/or improper performance of its duties towards combatants; outline the principles of UBD social protection; to determine directions of state policy in the field of social protection of participants of hostilities; etc. The adoption of such a regulatory act is expected to: first, improve the quality and efficiency of social protection of combatants; secondly, it will simplify the work of the state authorities.

Определены возможные пути усовершенствования законодательства, определяющего правовые основы социальной защиты участников боевых действий. Отмечено, что решить большинство имеющихся проблем возможно из-за унификации соответствующего законодательства путем принятия единого кодифицированного нормативно правового акта, а именно – «Основ законодательства о социальной защите участников боевых действий и их семей».
Keywords: соціальний захист; social protection; социальная защита; учасники бойових дій; participants in military operations; участники боевых действий; законодавство; legislation; законодательство; правові засади; legal principles; правовые основы